Evolution of virulence in eukaryotic microbes - Sibley, L. David; Howlett, Barbara J.; Heitman, Joseph (Hoboken, N.J. : Wiley-Blackwell, 2012)
"Combines advances in understanding virulence and evolution in three distinct fields; oomyctes, fungi and protozoan parasites - The first book to synthesizes advances in functional and comparative genomics represented in primary scientific literature for this topic. - Summarizes genetic tools in a diverse set of pathogenic organisms"--
pt. 1. General overviews -- pt. 2. Population genetics and evolutionary approaches -- pt. 3. Forward and reverse genetic systems for defining virulence -- pt. 4. Comparative "omics" approaches to defining virulence.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Protista; Eukaryotic cells; Microbial genomics; Virulence (Microbiology) -- Genetic aspects; SCIENCE -- Life Sciences -- Evolution; Eukaryotic cells; Microbial genomics; Protista; Virulence (Microbiology) -- Genetic aspects; Electronic books; Electronic books